Developments in sustainable manufacturing management : key concepts and tools - Singh, Chandan Deep (Emerald Publishing Limited, 2025)
The existing manufacturing environment lacks the integration of intelligent technologies and sustainable industrial development (SID) needed to boost production and create a cleaner, superior environment. Developments in Sustainable Manufacturing Management: Key Concepts and Tools introduces some mechanisms required to evaluate the environmental impact of intelligent techniques in contemporary organisations. The book also advocates for the use of alternative renewable energy sources, the establishment of zero-emission and zero-waste manufacturing facilities, and the promotion of green standards and awareness. The book examines Sustainable Industrial Development (SID) and Inclusive Sustainable Industrial Development (ISID) initiatives, and how these can contribute to the 2030 agenda for sustainable development. There is an increasing importance of sustainability in meeting regulatory and consumer demands, especially in the automotive industry. Developments in Sustainable Manufacturing Management serves as a guide for manufacturers, researchers, and policymakers aiming to maintain competitiveness in the global market through ISID, whilst considering technological and economic aspects.
Includes index.
Keywords: Sustainable engineering.; Business & Economics -- Industries -- Manufacturing.; Manufacturing industries.; elektronické knihy; electronic books